EKSISTENSI CERITA RAKYAT DI DESA BEJIHARJO, GUNUNGKIDUL DAN FAKTOR DETERMINAN YANG MEMENGARUHINYA - NFN Haryanto; Mei Latipah; Ari Kusmiatun (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2017)
The purpose of this study is to determine the existence of folktales and the determinant factors that affect it. This research uses a qualitative method of an ethnography type . The method of the data collection is done by observations and interview techniques; moreover, the data were analyzed by a qualitative technique . The validity of data is done by source, method, and theory triangulation techniques . The results of this research indicate that there are several folktales owning high-existence in the society of Bejiharjo Village, Karangmojo, Gunungkidul . The folktales which thrive in this village are a legend and a myth as Tradisi Bersih Kali, Legenda Goa Pindul, Tragedi Kali Semilih, Asal-usul Goa Sriti, Legenda Telaga Wilis, dan Sejarah Padukuhan Grogol. The existence can be seen as the clean ritual of the river which in its implementation refers to the folktales’ values of clean river tradition . Additionally, the folktales are also stated in the inscription on the t-shirts that are sold around the tourist attractions in Goa Pindul. The existence is influenced by internal and external factors. The internal factors are (1) the belief system of the society and (2) the presence of the elders and the traditional authorities in the Bejiharjo Village, while the external factors are (1) the historical relationship between the Sultan Palace of Yogyakarta and the Bejiharjo communities and (2) the high interest of tourists in Bejiharjo Village .